Prosecutorial Decision Making in Domestic Violence Cases: Are Prosecutors Holding Offenders Accountable? - Wagers, Shelly (Journal of interpersonal violence, 2023)
Domestic violence (DV) continues is an ongoing costly issue for the criminal justice system, Research indicates the prosecutor’s filing decision is important to keeping DV victims safe, but there is little research examining prosecutorial filing decisions in DV cases. This study used focal concerns as a theoretical framework to explore which legal and extra-legal factors impact prosecutorial filing decisions in DV cases. The study utilized data collected from 731 misdemeanor and felony DV cases from an urban County in Florida between January 2017 – December 2018. Two binomial logistic regression models were used to predict the likelihood a DV case would be filed on any charge, filed on a DV specific charge or not filed. Results showed some support for focal concerns but findings suggest that factors impacting this decision vary based upon case severity (i.e. misdemeanor, felony). A weapon present decreased the filing likelihood for misdemeanor cases but victim requests not to prosecute and a public attorney decreased filing likelihood for felonies. The prosecutor’s decision to file charges is a powerful tool to keep victims safe and should be based on legal facts and risk of future harm, but here these factors had little to no impact on this decision.